Indonesian English Teachers’ Work Engagement and Attitudes towards the Use of Instructional Technology: A Survey Study - Adaninggar Septi Subekti; Lemmuela Alvita Kurniawati (VELES Voices of English Language Education Society, 2022)
The present study was conducted to investigate the level of work engagement of Indonesian high school teachers of English and its relationship with their attitudes towards the use of instructional technology (IT) during the Covid-19-driven online instruction. The study employed a survey method of distributing a Google Form questionnaire and a total of 114 teachers participated in the study. It was found that the participants generally reported a high level of work engagement in their English Language teaching (ELT) profession. Though at least 93% of the participants reported their engagement in the profession in all questionnaire items, they seemed to be less sure about their level of engagement in terms of striving for excellence in the profession seen from lower "strongly agree" responses. The present study further found a statistically significant positive relationship between the participants' level of work engagement and their attitudes towards the use of IT during the pandemic-driven online instruction. Their level of engagement could predict a 21.7% variance in their attitudes towards the use of IT. Pedagogical implications include encouraging teachers to use all the experiences they obtained during the pandemic to upgrade themselves as teachers rather than totally 'going back' to the old ways of teaching before the pandemic. Future studies could investigate English teaching as a job and can be conducted qualitatively to see the extent to which teachers’ reported engagement is manifested in everyday teaching.